Editorial - Committee, Editorial (Austral Journal of Veterinary Sciences, 2017)
This is the second number of the “Austral Journal of Veterinary Sciences” formerly “Archivos de Medicina Veterinaria”. The name differs, but the aim of the Journal remains the same: “to divulgate the latest developments and discoveries in Veterinary Sciences and to inform about advances in veterinary medicine among universities, research centers, industries, government agencies, biologists, agronomists and veterinarians”. Today, as always, we face many complexes challenges and we do our best to tackle them.